Correlation between exclusive breastfeeding and obesity among children at kindergartens in Una-Una Central Sulawesi - Dipta Tejo Nugroho; Sepfrita Katerine Aftabuddin (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2022)
Obesity has become a global health problem that strongly correlates with morbidity and mortality. Despite the importance of obesity, there remains a paucity of evidence on obesity among kindergarten children in Tonjouna, Central Sulawesi. Obesity in children is influenced by various factors, one of which is exclusive breastfeeding. This study aims to find the correlation between exclusive breastfeeding and obesity among children aged four to six years in three kindergartens in Una-Una. The study uses a cross-sectional design involving all children at this kindergarten.   Anthropometric measurement was carried out in school before questionnaires were distributed to determine the number of breastfeeding given to the children. The data analysis revealed that 25% of children suffer from obesity. Five out of 68 children or 29.4% of those who get exclusive breast milk suffer from obesity. The statistical analysis using the Chi-square test shows a p-value of 0.002 (p<0.05), which means that exclusive breastfeeding correlates with obesity in children aged four to six years. This is rather disappointing that the percentage of obesity is relatively high. Hence, educating parents and schools about the causes, risks, and ways to prevent obesity is necessary.